Pengaruh Volatilitas Nilai Tukar terhadap Ekspor - Arif Rahman Hakim (STIE Widya Manggala, 2008)
The purpose of this papper is to examine relationship export with variable affect of Indonesia ti its six major trading partners (US, Japan, China, Singapore, Malaysia, and Thailand). By using cointegration approach and error correction mechanism, the study case is Indonesia export for period 1980-2006. Factors that affect Indonesia export are real foreign income, relative price and exchange rate volatility.This papper found that the exchange rate volatility has a significant negative effect on export expect Japan. It shows some exportes attitude is to avoid risk. But foreign income has significant positive effects om export. Relative price has a significant negativeeffect, just for export Indonesia to US, Singapore, and Thailand.